Konsep Pemikiran Pendidikan Islam Fazlur Rahman - Irwansyah Suwahyu (Referensi Islamika: Jurnal Studi Islam, 2024)
This article examines the educational thoughts of one of the reformers of Islamic education, namely Fazlur Rahman. This research is library research where data is obtained through documents which are analyzed using content analysis. The results of this research show that Islam prioritizes education in the lives of its adherents. Educational goals must be formulated with a balanced orientation between worldly life and the hereafter. Educators have a fundamental role in education, so educators need serious attention. Adequate things such as incentives for improving the careers of educators are urgently needed. Every educator must never stop learning and developing himself. They must have a high commitment to education. Students must also be taught the Koran as the main basis of their life. By learning the Koran well, it will provide a better understanding and meaning of life. And students will use the Koran as inspiration and motivation in their lives.